Palladium-Catalyzed Direct 1,4-Addition of Heteroarenes to α,β-Unsaturated Ketones via C–H Activation - Zhang, Xuan; Yu, Xiaoqiang; Feng, Xiujuan; Bao, Ming (Synlett, 2012)
Palladium-catalyzed direct conjugate additions of heteroarenes to α,β-unsaturated ketones via C–H activation are described. The reactions of heteroarenes with α,β-unsaturated ketones proceeded smoothly in the presence of PdCl2 as a catalyst under mild conditions to give the corresponding Michael adducts in moderate to excellent yields.
Keywords: palladium catalyst; direct conjugate addition; heteroarene; unsaturated ketone; C–H activation